Analisis Partisipasi Masyarakat Dan Peran Perangkat Desa Terhadap Pembangunan Desa Labuhan Kertasari, Kecamatan Taliwang, Kabupaten Sumbawa Barat - Nurifa Irma Suryani; Sri Rahayu (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2025)
This study examines the role of community participation and village officials in the development of Labuhan Kertasari Village, Taliwang District, West Sumbawa Regency. Sustainable and inclusive village development requires synergy between active community participation and the effective role of village officials. This study aims to analyze the influence of community participation and the role of village officials on village development. A quantitative method was used in this research. The population in this study consists of all residents of Labuhan Kertasari Village, Taliwang District, West Sumbawa Regency, totaling 2,326 people. Primary data were collected through questionnaires from 100 respondents. Data analysis was conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results show that both community participation and the role of village officials have a positive and significant effect on village development. Active community involvement in every stage of development, from planning to supervision, is crucial to ensure that development aligns with local needs. Competent and transparent village officials in managing village resources are also key factors in the effectiveness of development. Community participation and the role of village officials are essential factors in sustainable and inclusive village development. The implications of this study highlight the need to improve the capacity of both the community and village officials, ensure transparency in village fund management, and foster good collaboration among all relevant stakeholders to achieve more effective and equitable village development.